The influence of expertise on anticipation of badminton single serves - Kamruddin, E.; Mannan, S. (International Journal of Racket Sports Science, 2019)
Badminton is a fast racket sport and requires players to develop highly advanced anticipation skills. Research has identified differences in the way that experts badminton players fixate their gaze during play. Investigating eye movement patterns in badminton players, may help to understand how expertise is associated with better anticipation abilities. All previous research on the return of a badminton serve has been solely made up of laboratory-based components and consequently it is arguable as to whether athletic skills are transferable from real-life settings. This study investigated the return of a badminton serve in a game setting. Expertise and type of serve acted as the independent variables when investigating between-group differences during fixation development. The experts (N=23) and novices (N=11) were asked to return forehand serves, whilst wearing a mobile eye tracker, for recordingeye movement data for refixations, first visual intake duration and dwell time. The results demonstrated that both experts and novices targeted similar fixation sites. However, during the short serve, experts were found to make more fixations and longer fixation durations, suggesting that experts may use their pre-existing knowledge about badminton in anticipating serve returns.